The effect of plant growth regulators on optimization of tissue culture system in Malaysian upland rice - Shahsavari, Esmaeil; Abdul Aziz, Maheran; Abdullah, Siti Nor Akmar; Musa, Mohamed Hanafi (Academic Journals, 2010)
Mature seeds of four upland rice cultivars namely Kusan, Lamsan, Selasi and Siam were assessed for callus induction and plant regeneration on different concentrations and combinations of plant growth regulators, incorporated into MS (Murashige and Skoog) basal medium. Callus induction frequency was significantly different among the cultivars, as well as among the 2,4-Dichlorophenoxyacetic acid (2,4-D) levels tested. All tested cultivars exhibited highest callus frequency at 2 mgl-1 2,4-D. The incorporation of α-naphthaleneacetic acid (NAA) and kinetin (Kin) in the callus induction medium supplemented with 2 mgl-1 2,4-D did not significantly improve the callus induction frequency. After two subcultures, at 24 days interval, the best response to callus induction was from cultivar Selasi, while callus browning became prominent in cultivars Kusan and Siam. Embryogenic callus placed on different regeneration media exhibited the highest regeneration frequency on medium containing 0.5 mgl-1 NAA + 2.0 mgl-1 Kin + 2.0 mgl-1 6-benzylaminopurine (BAP). The maximum regeneration frequency was achieved in cultivar Selasi followed by Lamsan while Siam and Kusan exhibited poor regeneration response. Among the four upland rice cultivars evaluated, Selasi and Lamsan are two promising cultivars in terms of callus induction frequency and morphology, and regeneration ability of the embryogenic callus.